Modeling Lake Michigan Nearshore Carbon and Phosphorus Dynamics - (:unkn) unknown (My University, 2015)
Dreissenid mussels, in particular quagga mussels (Dreissena rostiformis bugensis), are transforming the Lake Michigan ecosystem by clearing the water column, recycling phosphorus and modifying benthic habitat. These impacts are thought to have caused observed declines in the spring phytoplankton bloom in Lake Michigan, as well as changes to food web structure and declines in the abundance of critical invertebrate and fish species. In the nearshore zone, the resurgence of benthic Cladophora algae to nuisance levels not observed since phosphorus loading abatement policies instituted in the 1970s has also been attributed to water column clearing and phosphorus recycling by mussels. Using a long term data set collected in the Lake Michigan nearshore zone between 1980 and 2013, changes in water quality parameters are characterized, compared to those monitored in the lake offshore, and analyzed in the context of the dreissenid mussel invasion and nearshore Cladophora growth. Using this time series analysis as a historical foundation, a computer model of the Lake Michigan nearshore zone was used to identify and quantify the influence of dreissenid mussels on Cladophora growth and nearshore phosphorus and carbon pools and fluxes. This is the first study of Lake Michigan to incorporate both dreissenid mussels and Cladophora algae in a dynamic phosphorus and carbon model. Model output for the summer and fall of 2013 was validated by comparison with an extensive data set of phosphorus and carbon measurements taken at a monitoring station at 9m depth in the Lake Michigan nearshore. The monitoring station and model domain are characterized by rocky substrate and quagga mussel densities of ~5500 individuals m-2 and summer, peak Cladophora biomass of 250 gDW m-2. Following model validation, model test scenarios were simulated excluding mussels. Comparison of model simulations with and without mussels confirmed that dreissenid mussels in the Lake Michigan nearshore zone support Cladophora growth at nuisance levels by increasing light penetration and phosphorus recycling. The nearshore mussel-Cladophora complex substantially increased the storage of phosphorus and carbon in the nearshore zone, supporting the nearshore shunt hypothesis. Mussels were found to support Cladophora production at levels which produced a net autotrophic nearshore zone with Cladophora production consistently exceeding mussel respiration and phytoplankton production during the summer. Due to tissue C:P ratios that were more than twice those of phytoplankton, Cladophora was able to utilize the available light and phosphorus provided by mussel grazing and recycling of phytoplankton to support high growth rates and to produce a large biomass. Even though the nutrients available for Cladophora growth came from phytoplankton recycled by mussels, the ability of Cladophora to store phosphorus in tissue and grow at a high rate with a high tissue C:P ratio lead to a net autotrophic nearshore ecosystem. Nearshore phytoplankton were consistently mixed into the model domain from the lake offshore due to mussel grazing and water column clearing. The consistent input of offshore particulate phosphorus and carbon to the nearshore in model simulations suggested that the nearshore is dependent on offshore energy sources. Tributary loading of carbon and phosphorus can subsidize mussel grazing and therefore limit the demand of nearshore mussels for offshore carbon and phosphorus. There are large areas of Lake Michigan, however, well away from river input that sustain large populations of mussels and Cladophora. These areas are likely sourcing energy and nutrients from the lake offshore as demonstrated by the results of this study. Although there is room for model improvement, the findings of this study provide the first definitive evidence that nearshore dreissenid mussels support Cladophora growth in the Lake Michigan nearshore zone and in doing so, create a seasonal nearshore sink for phosphorus and carbon supplied by the lake offshore. The results of this research provide guidance for future monitoring and modeling work which will provide a clearer picture of the influence of nearshore dreissenid mussels and Cladophora on whole lake nutrient dynamics and energy pathways.
Keywords: Carbon; Lake Michigan; Model; Mussels; Nearshore; Phosphorus